Influence of Job Engagement on Transformational Leadership Style and Organizational Performance - Ali, Khan Sarfaraz; Islam, Mezbah Ul; Azam, Tamanna Nowrin; Matin, Wares Ul (iRASD Journal of Management, 2021)
In recent years, job engagement has received considerable attention among academic community and business professionals. Still such issue needs to be prioritized in the research especially as it is an essential antecedent of organizational performance. This study aims at examining the relationship between transformational leadership style and organizational performance and to explore whether job engagement can influence on this relationship. Study data were collected from the employees working in a mobile phone company in Bangladesh and collected data were analyzed using SPSS version 20. In order to test the study hypotheses Partial Least Squares-Structural Equation Modeling (PLS-SEM) was used. The result of measurement model indicates that the relationship between transformational leadership style and organizational performance is statistically significant. In terms of mediation effects, job engagement mediates the relationship between transformational leadership style and organizational performance.